2022
DOI: 10.1002/jcc.26834
|View full text |Cite
|
Sign up to set email alerts
|

A real space picture of the role of steric effects inSN2reactions

Abstract: Within substitution reactions, the Bimolecular Nucleophilic Substitution (SN2) reaction mechanism is one of the most frequently found and studied ones. Among other factors, the easiness of the SN2 pathway is classically considered to be determined by steric hindrance. However, the diffuse nature of the latter inevitably darkens these and other arguments holding the pillars of chemical intuition. In this work, we employ the steric energy (EST) descriptor, formulated within the Interacting Quantum Atoms approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…For each anion series, the trend that KIEs became increasingly more normal (k H /k D > 1) as the extent of substitution indicated that the E2 pathway became the predominant pathway and steric effects inhibited the S N 2 pathway. A method calculating "steric hindrance (SH)" was proposed by Pendás and co-workers [39,40], which was consistent with the chemical intuition that the SH of the complex methylated alkyl system S N 2 was greater than E2.…”
Section: Introductionmentioning
confidence: 68%
“…For each anion series, the trend that KIEs became increasingly more normal (k H /k D > 1) as the extent of substitution indicated that the E2 pathway became the predominant pathway and steric effects inhibited the S N 2 pathway. A method calculating "steric hindrance (SH)" was proposed by Pendás and co-workers [39,40], which was consistent with the chemical intuition that the SH of the complex methylated alkyl system S N 2 was greater than E2.…”
Section: Introductionmentioning
confidence: 68%
“…Mevinphos has two –O–CH 3 groups, which do not generate an important steric hindrance due to the relative bulkiness of these groups. 57 Therefore the phosphorane intermediate appears in a shorter Nu–P distance. As shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Bimolecular nucleophilic substitution (S N 2) and elimination (E2) are ubiquitous, often mutually competing, reactions. For nearly 50 years, the mechanism of the S N 2 reaction has been extensively studied experimentally and theoretically, including its temperature dependence, 1–3 benchmark studies, 4–11 steric effects, 12–21 and solvent effects. 14,15,22–29 Solvation can have a tremendous effect on chemical reactions.…”
Section: Introductionmentioning
confidence: 99%